1‐Methylcyclopropene treatment controls ethanol accumulation associated with regulation of mitochondrial energy metabolism in kiwifruit (Actinidia deliciosa) cv. "Bruno" during storage at room temperature. Issue 7 (25th May 2020) - Ali, Maratab; Raza, Muhammad Ammar; Li, Shenge; Huan, Chen; Zheng, Xiaolin
Abstract: In this paper, the effects of 1‐methylcyclopropene (1‐MCP) treatment on the ethanol accumulation and mitochondrial energy metabolism in kiwifruit ( Actinidia deliciosa ) cv. "Bruno" were investigated during storage at room temperature (24 ± 1°C). The results showed that 1‐MCP treatment significantly reduced the ethanol accumulation, maintained higher levels of adenosine triphosphate (ATP) content and energy charge (EC), enhanced enzymes activities involved in mitochondrial energy metabolism, such as succinic dehydrogenase, cytochrome C oxidase, H + ‐adenosine triphosphatase (H + ‐ATPase), and Ca 2+ ‐adenosine triphosphatase (Ca 2+ ‐ATPase), and regulated the NADH/NAD + ratio, and pyruvate to tricarboxylic acid cycle (TCA) by suppressing the glutamate–pyruvate transaminase and promoting the pyruvate dehydrogenase activity, and decarboxylation of citric acid in harvested kiwifruit. These shifts in mitochondrial energy metabolism and oxidative phosphorylation correlated the higher ATP yield and an elevated EC with lower ethanol accumulation (13.71% of those in the control fruit) under 1‐MCP treatment, and reduced the susceptibility of ethanol related off‐flavor disorder in kiwifruit during storage. Practical applications: A kiwifruit ( Actinidia deliciosa ) cv. "Bruno, " a major cultivated kiwifruit in China, is prone to accumulate ethanol sharply after respiratory climacteric during storage. Ethanol has been accounted as a vital aroma volatile metabolite in various fruits. However, over accumulation of ethanol often leads to the development of alcohol off‐flavor disorder, particularly in typical climacteric fruit such as kiwifruit. This work was aimed to maintain the flavor quality of kiwifruit cv. "Bruno" via improving the mitochondrial energy metabolism and functional TCA cycle, and limiting the ethanol accumulation under 1‐MCP treatment. Thus, 1‐MCP treatment could be beneficial to prevent the occurrence of alcohol off‐flavor disorder along with sustainment of the flavor quality of kiwifruit cv. "Bruno" during storage at room temperature. Abstract : 1‐MCP treatment controlled ethanol accumulation via regulating the higher ATP and EC in kiwifruit cv. 'Bruno' during storage. 1‐MCP treatment regulated the mitochondrial energy metabolism‐related enzymatic activities. 1‐MCP treatment maintained oxidative phosphorylation by regulating TCA and NADH/NAD + ratio.